Performance Analysis of Permanent Magnet BLDC Motor for Reducing Cogging Torque Using Taguchi Method - Ferdyanto, Ferdyanto; Fatwa, Gumilang; Erlangga, Augusta; Marbawi, Idris (ELKHA : Jurnal Teknik Elektro, 2024)
An electric motor is an electromagnetic machine commonly utilized across various industries and automotive products. One prevalent type of electric motor employed in electric vehicles is the Permanent Magnet Brushless DC Motor (PM-BLDC), a brushless motor employing permanent magnets. However, despite its efficiency, permanent magnet motors often experience vibrations that can disrupt their performance. This research aims to optimize the existing BLDC motor design, with a specific focus on reducing the existing cogging torque. Initially, the existing design exhibited a cogging torque level of 0.21482 Nm. The optimization process involved modifications to several key design parameters, such as air gap, magnet thickness, magnet type, and slot opening width. In previous research, only comparisons were made between stator slot designs, which proved to be less effective as significant differences were not evident in the results of the comparative analysis of BLDC motor designs. So, in this research, the Taguchi method was utilized for the optimization process due to several advantages it offers. Through an analysis of means and variance, the optimization process successfully achieved a significant reduction in cogging torque by 0.099744 and an increase in efficiency by 0.6%. The results of the optimized permanent magnet BLDC design indicated a cogging torque value of 0.115072 Nm and an efficiency of 86.64% at an operational motor speed of 1500 rpm. This research provides a substantial contribution to the development of more efficient electric motors suitable for various applications.